Minimally-Myelosuppressive Asparaginase-Containing Induction Regimen for Treatment of a Jehovah's Witness with mutant IDH1/NPM1/NRAS Acute Myeloid Leukemia - Ashkan Emadi; Najeebah A. Bade; Brandi Stevenson; Zeba Singh (MDPI AG, 2016)
Treatment of patients with acute myeloid leukemia (AML) who do not wish to accept blood product transfusion, including Jehovah's Witnesses, is extremely challenging. The use of conventional chemotherapy for induction of complete remission (CR) results in profound anemia and thrombocytopenia requiring frequent transfusions of blood products, without which such treatment will be life-threatening. Finding a well tolerable, minimally myelosuppressive induction regimen for such patients with AML is a clear example of area of unmet medical need. Here, we report a successful treatment of a 52-year-old Jehovah's Witness with newly diagnosed AML with peg-asparaginase, vincristine and methylprednisolone. The AML was characterized with normal karyotype, and mutations in isocitrate dehydrogenase 1 (IDH1-Arg132Ser), nucleophosmin 1 (NPM1-Trp289Cysfs*12) and neuroblastoma RAS viral oncogene homolog (NRAS-G1y12Va1). After one 28-day cycle of treatment, the patient achieved complete remission with incomplete count recovery (CRi) and after the second cycle, he achieved CR with full blood count recovery. The patient has never received any blood products. Notwithstanding that myeloperoxidase-induced oxidative degradation of vincristine results in its lack of activity as monotherapy in AML, its combination with corticosteroid and asparaginase has resulted in a robust remission in this patient. Diminished steroid clearance by asparaginase activity as well as reduction in serum glutamine level induced by glutaminase enzymatic activity of asparaginase may have contributed to effective killing of the myeloblasts that carry IDH1/NPM1/NRAS mutations. In conclusion, asparaginase-containing regimens, which are approved for treatment of acute lymphoblastic leukemia (ALL) but not AML, can be used to treat patients with AML who do not accept blood transfusion.